The Study of the Effects of Acetobacter Isolated from Local Picklesin PTEN/AKT Signaling Route in Colon Cancer Cells (HT29) - Pariya Azarng; Changiz Ahmadizadh (Majallah-i Dānishgāh-i ’Ulūm-i Pizishkī-i Īlām, 2019)
Introduction: The imbalance of the microbial ecosystem causes biological changes associated with colorectal cancer and cell proliferation and their planned death, as well as the immune responses. The aim of this study was to determine the effect of probiotic bacteria on the expression of genes associated with growth, metastasis and apoptosis in cancer cells of the HT29 colon.